Design Guidelines for Wearable Pointing Devices - Zucco, Joanne E.; Thomas, Bruce H. (Frontiers in ICT, 2016)
This paper presents design guidelines and recommendations for developing cursor manipulation interaction devices to be employed in a wearable context. The work presented in this paper is the culmination three usability studies designed to understand commercially available pointing (cursor manipulation) devices suitable for use in a wearable context. The set of guidelines and recommendations presented are grounded on experimental and qualitative evidence derived from three usability studies and are intended to be used in order to inform the design of future wearable input devices. In addition to guiding the design process, the guidelines and recommendations may also be used to inform users of wearable computing devices by guiding towards the selection of a suitable wearable input device. The synthesis of results derived from a series of usability studies provide insights pertaining to the choice and usability of the devices in a wearable context. That is, the guidelines form a checklist that may be utilized as a point of comparison when choosing between the different input devices available for wearable interaction.